Refusing to Eat Pre-chewed Food: Assessment of the Effectiveness of ‘Jitegemea Philosophy’ in the Ecclesiology of the PCEA in Nyeri and Ki rinyaga Counties Kenya (1971-2021) - Kariithi , Alice (African Journal of Education,Science and Technology (AJEST), 2022)
The call for moratorium on foreign missionaries and subsequent adoption of the ‘Jitegemea’ philosophy in the Presbyterian Church of East Africa (PCEA) provoked a strong debate about the future of the church and her ability to engage in misiological aspects without external support. The African Church was sim ply refusing to eat pre-chewed food from missionaries. The philosophy was expected to guide the Church into self-sufficiency in terms of finances, evangelization, theologizing and governance and personnel. Consequently, income generating projects such as building of schools, hospitals and farming among other were established to support the needs of the church. However, limited research has been conducted to examine the challenges and lessons learnt by the PCEA especially at the Parish level since the moratorium was commenced. The purpose of this study therefore, is to examine the positive outcomes of the moratorium on the growth of the PCEA, to assess the challenges faced by the PCEA since the Jitegemea philosophy was adopted in 1971 and the lessons learnt fifty years later. A survey research design using a mixed method approach was adopted. Data collection was done using questionnaires for ordinary church members and interview guides for both church elders and parish ministers. Quantitative data was analyzed descriptively using percentages, means and frequencies. Qualitative data was analyzed by organizing it into themes based on research objective. The study established that since moratorium was started the PCEA in Nyeri and Kirinyaga Counties has benefited through establishment of self reliance, self propagation, selftheologising and self-governance structures. However, the Jitegemea philosophy increased financial burden to the members with some wishing for financial support from churches of the western countries. The study recommended the establishment of more vibrant church policies that can accommodate support from global Church as a way of encouraging partnership in mission and development.